Features Changes Hemodinamic Liver Easy Preeclampsia - Zaripova D.Ya (Research Parks Publishers, 2024)
Examine the systemic circulation of the liver and its role in the predicting of preeclampsia. We studied 100 pregnant women with mild preeclampsia (II group), and 50 pregnant women with physiological pregnancy control group (I group), 50 pregnant women with severe PE (III group). Comprehensive ultrasound and Doppler blood flow study was performed, ultrasound scanner Sono-scape SSI 5000 (China model) equipped with Convex probe (3.5 MHz) provided with a pulsed Doppler unit and wave function of the DRC. Examined blood flow in arteries and veins of the liver (liv A, liv V, Col V). Blood flow in the same hepatic portal vein and a tendency towards a certain decrease in pregnant women with PE. LMS and R & D in the hepatic artery, these values were increased by 13.3 and 26.4, respectively, in severe PE. Study features of hepatic arterial blood flow with the emergence of hypertension in pregnancy can be a predictor of the development of PE and its progress with the transition to severe.